CORRELATION BETWEEN BAMBOO UTILIZATION AS EARTHQUAKE RESISTANT HOME CONSTRUCTION MATERIALS WITH COMMUNITY BEHAVIOR IN MAINTAINING ENVIRONMENTAL SUSTAINABILITY - Indrianeu, Tineu (JURNAL PENDIDIKAN ILMU SOSIAL, 2017)
In 2009 Jayapura Village was hit by an earthquake with a strength of 7.3 on the Richter Scale. Many homes were damaged by the quake. The purpose of this study is to analyze the relationship between the utilization of bamboo as a home building material with environmental preservation behavior of Jayapura Village residents. The study population was 1,367 heads of households with a sample of 137 families. The method used in this research is using sequential mixed methods. The result of the research shows that there is a correlation between the two things which is indicated by the correlation value of 0,501 (medium correlation).